(untitled) (Theatrum historiae, 2008)
The case of Göttingen is a clear example of how crucial the maternity hospital was in Germany, both for the emergence of man-midwifery and for turning midwifery into a ‘science’. In this regard, the Göttingen case is clearly closer to the conventional wisdom about the role of lying-in hospitals than, for example, the maternity hospital of Port-Royal in Paris, which was directed by the chief-midwife and trained only female midwives. In spite of this, even the Göttingen hospital was far from being able to transform women into mere cases and objects of the emerging obstetrical science. The women who decided to deliver in the hospital tried to use this institution for their own purposes as much as they could. With regard to the relationship between medical men and female midwives, the picture that emerges from a closer scrutiny of German sources is also more complicated than expected. Well into the twentieth century and in spite of their often wild polemics against traditional midwives, German obstetricians, including those at the University of Göttingen, did not really mean to replace them with medical doctors. The number of doctors was far too small to attend every delivery, and most families were much too poor to pay a fee adequate to a university-trained man. Doctors wanted to control and instruct midwives, not to take their place. That is why even most university lying-in hospitals trained medical students and midwives. Most doctors were willing to attend deliveries themselves only with well-todo ‘private’ patients, and in difficult cases. The point was not so much a new division of labour between midwives and medical men, but rather a shift in the distribution of power and authoritative knowledge. This ambivalent attitude to midwives becomes visible even in the Göttingen maternity hospital, if we carefully analyse its educational policy. Around 1800, in 78 per cent of the cases, the birth attendants were male (medical students and professor Osiander), and only in 22 per cent, the attendants were female (midwife apprentices and the hospital midwife). Furthermore, in every semester, the number of medical students trained at the hospital was five to ten times higher than that of the midwife apprentices. This confirms professor Osiander’s statement that the first aim of this institution was educating medical men, and that training midwives was only second priority. Because of the much greater number of medical students, however, the opportunities for practical training per person were clearly fewer for medical students than for midwife apprentices. One third of all the medical students who took the course in obstetrics never participated hands-on in a delivery, but only watched. And the majority of those who did were in charge of only one birth. On the other hand, the majority of midwife apprentices were involved, hands-on, in several deliveries. This probably means that most of the medical students, even of those trained at the Göttingen maternity hospital, had a lot of practical skills to acquire after their university years, in their own practice. Beginning in the late eighteenth, definitively by the second half of the nineteenth century, the directors of maternity hospitals and professors of obstetrics in Germany had achieved their goal: they were, at least in the eyes of governments and the educated male public, acknowledged as the leading experts in childbirth. The reasons why they succeeded deserve further investigation, for measured by their own aim of saving mother’s and children’s lives their achievements appear to be less than convincing. Throughout Europe, the maternal mortality rate was higher in hospitals than for normal home deliveries attended by midwives. The main reason was of course puerperal fever, a highly infectious disease. It is true that the record is better for Göttingen’s lying-in hospital than for its larger counterparts. But maternal mortality in hospitals worsened towards the middle of the nineteenth century. These mortality data were well-known to, and publically discussed by experts. Whatever the achievements of maternity hospitals were in the eighteenth and nineteenth centuries, reducing maternal mortality was not among them, at least not for deliveries which took place within the hospital walls.